Nephropathia epidemica: incidence of clinical cases and antibody prevalence in an endemic area of Sweden. - Niklasson, B. (Cambridge University Press, 1987)
The incidence of nephropathia epidemica (NE) was compared with the NE antibody prevalence in normal population in a highly endemic area of Sweden (Västerbotten county). The antibody prevalence rate in the oldest age groups were found to be 14 and 20 times higher than the accumulated life-risk of being hospitalized with NE for men and women respectively. Whether the infection in persons not admitted to hospital is subclinical, atypical or clinically fulminant, remains to be determined.